Perancangan Media Visual Komik Fisika Pada Materi Pembelajaran Pelangi - Yekezia Efatasari Putri; Diane Noviandini; Marmi Sudarmi (Radiasi : Jurnal Berkala Pendidikan Fisika, 2019)
The purpose of this study was to make comics as a learning media which could emerge student’s interest in reading, especially for physics lesson and as a means of literacy. The method used was ADDIE (Analyze, Design, Development, Implement, and Evaluation). The phase of Analyze included the determination of the test subject, the software to be used, and the material reference. The stage of Design included the creation of scripts, test concepts, and form indicators. The development stage consists of making comics, testing media experts and concepts, and also doing repairs and printing. The phase of implementation consists of testing on test subjects, specifically 23 Junior High School students. The implementation of comic testing for Junior High School students used observation sheets of the data collection instruments filled by the observers; meanwhile, the test questions and questionnaires filled by the students. In the phase of Evaluation, the data obtained processed qualitatively and quantitatively. Through the tests given after the learning process, it found that 86.9% of the test subjects got a score of 75. There revealed that the comic titled RAINBOW succeeded in explaining the concept of the rainbow process. The results of the questionnaire found that 89.08% of all aspects of the comics' physical form were good and deserved to used as a learning media. Besides, the comic itself could be a means of literacy, and also the students became interested in learning physic. The results of assessment and observations by observers during the teaching and learning activities also stated that the students.